A 3 dB SISL coupler design by multi‐objective evolutionary algorithm based on decomposition. Issue 12 (28th October 2022) - Zhang, Yongliang; Yi, Yu; Feng, Linping; Qi, Guangfei; Zhang, Xianfang; Zhang, Xiaoping; Yang, Chen
Abstract: In this article, a 3 dB substrate integrated suspended line (SISL) coupler design by multi‐objective evolutionary algorithm based on decomposition (MOEA/D) is proposed. SISL technology can provide electromagnetic shielding performance and realize the low loss, lightweight, and self‐packaging. The highly time‐consuming problem of adopting traditional electromagnetic (EM) simulation software to assist coupler design is always the main problem for the design of couplers. To solve the problem, this article applies MOEA/D based on one‐dimensional convolutional autoencoders (1D‐CAE) to assist coupler design. 1D‐CAE model builds the surrogate model to help MOEA/D find out better responses faster. MOEA/D has some advantages of saving time and getting good performance easily.